The PENGUATAN LITERASI ANAK MELALUI PROGRAM KELAS PENULIS CILIK - Umi - Farkhatun (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
The background of this research is the low interest in reading Indonesian students as one of the literacy skills. As an alternative solution to this, effective literacy improvement programs are needed for children. This study aims to determine the effectiveness of child writer's class program as a program to strengthen children's literacy. The subjects were 20 young writer class participants at PKBM Ar Rosyid. The method used in this research is descriptive qualitative. The results showed that the child writer's class was effective in strengthening children's literacy because through an interesting learning method, the program had succeeded in publishing two anthology books written by 67 young writers.